2008
DOI: 10.1080/14622200802412929
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on mood and cigarette craving during early abstinence and resumption of smoking

Abstract: Women are more likely than men to relapse after initiating abstinence from cigarette smoking. The reasons for this phenomenon are unclear but may relate to negative mood, cigarette craving, or other symptoms of nicotine withdrawal. We addressed this issue in a study of 26 female and 38 male smokers. The Profile of Mood States, Shiffman-Jarvik Withdrawal Scale, and Urge to Smoke Scale were administered twice in each of two test sessions on different days. One session began within 1 hr after smoking ad libitum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 64 publications
11
75
0
3
Order By: Relevance
“…Women have more difficulty quitting than men (Perkins et al, 2001;Piper et al, 2010). They report more negative affect (Xu et al, 2008;Langdon et al, 2013;Doran, 2014) and greater cueinduced craving (Field and Duka, 2004;Carpenter et al, 2014;Doran, 2014) than men during acute withdrawal. Men tend to be more reinforced by the nicotine in cigarettes, that is, they are more sensitive to the nicotine level (Perkins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Women have more difficulty quitting than men (Perkins et al, 2001;Piper et al, 2010). They report more negative affect (Xu et al, 2008;Langdon et al, 2013;Doran, 2014) and greater cueinduced craving (Field and Duka, 2004;Carpenter et al, 2014;Doran, 2014) than men during acute withdrawal. Men tend to be more reinforced by the nicotine in cigarettes, that is, they are more sensitive to the nicotine level (Perkins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although women's vulnerability to nicotine/smoking dependence is likely determined by many factors (O'Dell and Torres, 2014;Perkins et al, 1999), considerable evidence suggests that women vs men are more sensitive to acute rewarding effects of smoking or nicotine administration. Some studies found that women experienced greater reductions in craving (Eissenberg et al, 1999) and tension-anxiety symptoms Effects of menthol on brain nicotine accumulation Y Zuo et al (Xu et al, 2008) immediately after cigarette smoking. Women reported stronger 'drug strength', 'head rush' from intravenous bolus nicotine (Sofuoglu and Mooney, 2009), and stimulant and mood-altering experiences after nicotine nasal spray (Myers et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados coinciden con diferentes estudios (Goodwin et al, 2011;Leventhal et al, 2007;Luk & Tsoh, 2010;Nakajima & al'Absi, 2012;Pang et al, 2015;Roys et al, 2016;Schleicher et al, 2009;Weinberger & McKee, 2012;Xu et al, 2008) en los que se muestra una asociación significativa entre la sintomatología depresiva y el afecto negativo en mujeres adultas y el nivel de dependencia. Sin embargo, los resultados obtenidos en el presente estudio incluyen la ansiedad como una variable que también se asocia con el patrón de consumo y al nivel de dependencia de la nicotina.…”
Section: Discusión Y Conclusionesunclassified
“…La literatura científica muestra que cuando las mujeres suprimen el consumo de tabaco presentan síntomas de abstinencia más graves que los hombres, es decir que se incrementan el afecto negativo (miedo, ansiedad, tristeza, irritabilidad, tensión, impaciencia, inquietud), la angustia relacionada con la abstinencia y el deseo de fumar para aliviarla, además de los problemas de concentración y los sín-tomas físicos desagradables (dolores de cabeza, sínto-ma autonómico y somnolencia; Leventhal et al, 2007;Pang & Leventhal, 2013;Perkins, Karelitz, Giedgowd, & Conklin, 2013). Dado que las mujeres experimentan sín-tomas de abstinencia severos, utilizan el cigarro como reforzador negativo para aliviarlos (Pang, Zvolensky, Schmidt, & Leventhal, 2015;Schleicher, Harris, Catley, & Nazir, 2009;Weinberger & McKee, 2012;Xu et al, 2008).…”
Section: Introductionunclassified